Development of Online Monitoring Device for Ash Accumulation Status of Alkali Recovery Boiler - Wang, Bo; Zhang, Caiming; Wang, Yuanli (Engineering Transactions, 2026)
The alkali recovery boiler is an important piece of equipment in chemical pulp production. It uses papermaking black liquor as fuel. Due to the large number of impurities, the heating surface is prone to severe ash deposition. To improve the heat transfer coefficient, the traditional method is to carry out timed soot blowing, which has problems such as untimely ash cleaning or excessive steam consumption caused by overly frequent soot blowing. In this paper, an experimental device for the relationship between the heat transfer coefficient and the weight of ash deposition was developed. The functional relationship between the two was obtained. There is an inflection point when the amount of ash deposition reaches 294.77 g. A control strategy of soot blowing at the inflection point was further proposed. A load-strain experimental testing device was developed. Experiments show that when the weight of ash deposition reaches 3503 N, the deformation of the suspender is 9 με, and starting the soot blowing device is the most efficient when the heat transfer coefficient is 725.15 W/(m²·K). Therefore, the degree of decline of the heat transfer coefficient can be indirectly reflected by measuring the strain. A method of soot blowing by detecting the degree of suspender strain was further proposed. This method is more scientific than the original timed soot blowing method and provides a technical reference for the energy-saving and consumption-reduction theories and engineering applications of alkali recovery boilers.